Show your worth : 8 intentional strategies for women to emerge as leaders at work - Abji, Shelmina (Business professional collection, 2022)
"Smart strategies for succeeding at work-tailor-made for female professionals in underrepresented communities For female professionals in underrepresented communities, scaling the corporate ladder comes with a unique set of challenges and obstacles. In Show Your Worth, Shelmina Abji shows you how the power of intention-developing and executing a clear aim and plan-can help you steer your way through the headwinds to achieve your goals. Abji writes from experience. As a child in East Africa who had never heard the term "senior corporate executive," she went from being the first college graduate in her family to one of the highest-ranking women of color at IBM. She attributes her success to the eight intentional practices she lays out in Show Your Worth, providing wisdom tailored to your experience-from how to value yourself and your own perspective to how to overcome fear and contribute at your maximum level. Smart, ambitious women who are underrepresented in their fields tend to rely solely on hard work and skills, Abji notes, so you'll also find wise counsel on how to nurture self-awareness, self-approval and self-trust, so you can succeed at the top without compromising your values. You'll discover how these Eight Intentional Practices can help you achieve success: Introspection: Define what career success means to you Attention: Develop your personal strategic plan Branding: The ins and outs of building and preserving your reputation Value: Overcome fear, find your voice, and contribute at your maximum level Relationships: Connect meaningfully with first-line managers, mentors and sponsors Positioning: How to be strategic about earning a promotion Choice: Achieve work-life balance in our disrupted world Growth: Expand your competence and confidence in everything you give and receive"--